A New Appliance for Class III Treatment in Growing Patients: Pushing Splints 3 - Stefano Martina; Roberto Martina; Lorenzo Franchi; Vincenzo D'Antò; Rosa Valletta (Hindawi Limited, 2019)
Several orthopedic procedures have been used in early treatment to reduce the need for orthognathic surgery in skeletal Class III. The most used treatment is Rapid Maxillary Expansion and Facemask. This procedure also determines a clockwise rotation of the mandible, increasing the vertical dimensions of the lower third of the face. Therefore, the control of vertical dimension appears to be a key objective in Class III hyperdivergent patients. This article shows two skeletal Class III patients treated with a new appliance (Pushing Splints 3), that is able to correct sagittal discrepancy with a good control of the vertical growth. In both cases, Class I relationship with a proper Overjet and Overbite was achieved with improvement of profile. The final cephalometric values demonstrated a stable sagittal relationship and a good control of the vertical growth. The specific biomechanic features of the PS3 appliance permit the improvement of the sagittal jaw relationship, delivering at the same time vertical vectors that are able to control the alveolar and skeletal components of the vertical growth. This could be useful in the treatment of Class III hyperdivergent patients.